Small-scale farming and gender-friendly agricultural technologies: the interplay between gender, labour, caste, policy and practice. (2nd September 2017) - Hansda, Regina
Abstract: In this paper, I examine the interplay among gender, labour, and technology within an emerging, alternative, rice-growing technique called the System of Rice Intensification (SRI) to understand how in situations of agrarian transition, technology affects and influences social dynamics. The technology under consideration in this paper is a small, labour-saving device, called the weeder, seemingly suitable for smallholder farmers, and often projected as a gender-friendly device. The purpose of this paper is two-fold. First, to discuss and demonstrate how intersections of gender, caste and class issues even within agro-ecological farming practices can result in experiences that can be highly differentiated. Second, to question and argue against the naturalization and/or apparent lack of problematization of production of such social difference and material outcomes. The paper draws theoretical insights from feminist political ecology (FPE) and feminist technology studies (FTS) and is based on an extended ethnographic fieldwork in Bihar, India.